Does social inducement lead to higher open innovation investment? An experimental study - Shuanping Dai; Guanzhong Yang (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2017)
Open innovation has attracted an avalanche of interests from many practitioners and scholars, and is gradually becoming an acceptable scientific and managerial paradigm over the past few decades. Traditionally, however, innovative activities ought to be confidential within certain groups or individuals before the marketing process, and will be protected strictly by the intellectual property rights laws, for the sake of innovators' economic benefits and encouraging further innovation attempts. This paper aims at addressing the question of how to stimulate firms and managers to invest more resources to open innovation, and focuses on social inducement's effectiveness, in the art of a pre-recorded video, using an experimental approach. We established two open innovation investment models in which investors decide to allocate resources to open and traditional innovation projects. In the first model, we introduce the spillover effect and assume that traditional innovation projects may profit from open innovation investment. We then consider uncertainty to make the investment more realistic in the second model. The effect of social inducement on open innovation provision has been investigated in all the three settings, i. e. No Video, Full Video and Half Video. The striking result is that social inducement increases open innovation investment, but only if both induced subjects and non-induced subjects exist; meanwhile, economic uncertainty also matters.
Keywords: C92; H41; O31; 330; open innovation; social inducement; conditional cooperation; economic uncertainty